Executive compensation and conflict between shareholders and creditors: Evidence from creditor litigation - Xiao Li; Yanchao Wang; Hong You (China Journal of Accounting Research, 2020)
Using creditor litigation data from China, we investigate whether creditors can participate in corporate governance when agency conflict between shareholders and creditors is severe. By comparing firms that have experienced creditor lawsuits (litigation firms) with those that have not (non-litigation firms), we find that litigation firms have lower pay-performance sensitivity before lawsuits, suggesting that these firms have weaker corporate governance. This result is consistent with our expectation that creditors participate in corporate governance by introducing external monitoring when internal monitoring, dominated by shareholders, is insufficient. We also find that the association is stronger for firms with more severe shareholder-creditor agency conflict. Moreover, creditor litigation is strongly related to low pay-performance sensitivity when the external legal environment is strong. Our results remain robust to different model specifications and after addressing endogeneity problems.
Keywords: 650; Corporate governance; Agency problem; Creditor litigation; Pay-performance sensitivity